A retrospective analysis of endoscopic septoplasty - Amarnath SB; Sushma SG; Kuppam RD; Guthi VR (Journal of Medical and Scientific Research)
Introduction: Septal deviation is a frequently found structural deformity causing nasal obstruction, headache, postnasal drip and snoring etc. With the advent of endoscopes, conventional headlight surgeries have been largely replaced. Endoscopic septoplasty is a minimally invasive targeted approach for septal correction.